DESIGN ZOLMITRIPTAN LIQUISOLID ORODISPERSIBLE TABLETS AND THEIR IN VITRO EVALUATION - Egla, Mustafa; Hammid, Shaimaa N. Abd Al (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of present study is to develop orodispersible tablets (ODTs) of zolmitriptan by liquisolid technique using different types of super disintegrants to enhance the disintegration and dissolution of zolmitriptan to improve the bioavailability of the drug. Methods: Liquisolid ODTs of zolmitriptan were prepared from; microcrystalline cellulose (Avicel PH-102) as carrier, colloidal silicon dioxide (Aerosil 200) as a coating material, croscarmellose sodium (CSS), sodium starch glycolate (SSG), and crospovidone (CP) as super disintegrants, and propylene glycol as liquid vehicle. The ratio of carrier to coating material was kept constant in all formulations at 35:1, this ratio was chosen after testing the ratios 10:1, 15:1, 20:1, 25:1,30:1, and 35:1. The ratio 35:1 give optimal results relative to other ratios. The pre-compression evaluation includes: flow properties were measured using the angle of repose and the compressibility index and FT-IR. The prepared liquid-solid system compacts were evaluated for their post-compression evaluation which includes: hardness, friability, wetting time, in vitro disintegration time, drug content and in vitro drug release. Results: The tabletting properties of the liquid-solid ODTs were within the acceptable limits. Among the three super disintegrants, CP found to be the best in term of showing the fastest disintegration time. The optimized selected formula (F11) was prepared using 5% w/w crospovidone, by direct compression showed the shortest disintegration time (24 s), superior drug release profile [ the time required for 80% of the drug to be released (T80%) and percent drug dissolved in 2 min (D2 min) 1.84 min and 87.59%, respectively]. In addition to that, the selected formula had an acceptable hardness and friability, so it was selected as the best formula. Conclusion: The overall results showed that CP was the best super disintegrant of showing the shortest disintegration time while loading factor of 0.125 was the best in the preparing of zolmitriptan liquid-solid ODTs, and this suggested the possibility of utilizing the selected best formula (F11) in the preparation of zolmitriptan ODTs as a new dosage form for oral administration.Â 